LEGAL CONSIDERATIONS REGARDING THE OFFENSE OF DRIVING UNDER THE INFLUENCE OF ALCOHOL - George Octavian NICOLAE (Challenges of the Knowledge Society, 2022)
Article 336 of the Criminal Code criminalizes the act of driving a vehicle on public roads for which the law provides for the possession of a driving license by a person who, at the time of taking biological samples, has an alcohol content of more than 0.80 g/l pure blood alcohol. In the legal doctrine and in the judicial practice there is a controversy regarding the effects of the legal disposition provided by art. 78 para. 2 of GEO. no. 195/2002, regarding the presumptive establishment of the blood alcohol value. Thus, in a first opinion, it is considered that in order to be able to retain the meeting of the constituent elements of the crime of driving a vehicle under the influence of alcohol, it is necessary to establish beyond any doubt that the perpetrator had a higher blood alcohol level than the established one by the rule of incrimination. In the second opinion, it is appreciated that the provisions provided by art. 78 para. 2 introduces a legal presumption, which establishes that the value of the blood alcohol level at the time of testing is also that at the time of driving on public roads, as a result of the author's violation of the obligation not to consume alcoholic beverages between the time of a car accident and timing of alcohol testing. In this article we will analyze the two opinions present in legal doctrine and judicial practice, as well as the decisions of the High Court of Cassation and Justice and the Constitutional Court in this matter.